The potential of the application of biodegradable and non‐toxic base oils for the formulation of gear oils — model and component scuffing tests. (12th March 2014) - Tuszynski, Waldemar; Szczerek, Marian; Michalczewski, Remigiusz; Osuch‐Slomka, Edyta; Rogos, Elzbieta; Urbanski, Andrzej; Almqvist, Andreas; Hardell, Jens; Prakash, Braham
ABSTRACT White and natural base oils are assessed as candidates for the formulation of ecological gear oils. They are compared to 'classical' mineral and polyalphaolefins‐based oils in scuffing four‐ball and gear tests. Four fully formulated gear oils were prepared by blending each base oil with the package of extreme pressure (EP) additives, an anti‐foam additive and an anti‐oxidant. It is shown that the resistance to scuffing of the white oil is comparable to the classical oils, but the natural (rapeseed) oil reduces resistance to scuffing, because the used EP additives may not be suited to the rapeseed 'matrix' producing adverse effects. Thus, rapeseed‐based gear oils can be used only for the lubrication of gears working under moderate load conditions. It is also indicated that, when comparing the mechanisms of tribochemical action of the EP additives in the four‐ball tribosystem and meshing teeth, care should be taken, because the conditions in the contact zones are different. Copyright © 2014 John Wiley & Sons, Ltd.